The Relationship between Serum Uric Acid Level and Pulmonary Artery Hypertension in Patients with Chronic Renal Failure - Somaye Jamali; Farokhlegha Ahmadi; Mitra Mahdavi-Mazdeh; Anahita Tavoosi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2019)
Background and aim: Uric Acid is the final production of purine metabolism. The serum concentration of this substance is related to purine metabolism and renal clearance. Pulmonary hypertension (PH) in patients with CKD may be induced or aggravated by left ventricular (LV) disorders. The presence of risk factors typical to CKD is including volume overload, an arteriovenous fistula, sleep-disordered breathing. Exposure to dialysis membranes, endothelial dysfunction, vascular calcification and stiffening, and severe anemia. Materials and methods: In this study relation between Uric Acid levels and PH in 70 patients with non-dialysis renal failure (41 females, 29 males) with a mean age of 61.71±12.44 years were assessed. The required information is extracted from the patients' records based on the questionnaire. Finally, the results are analyzed according to the SPSS program. Results: PH was defined as a PASP ≥ 35 mmHg by echocardiography. 36 CKD patients had PH (51.4%). Average Uric Acid levels in patients with PH were significantly higher than healthy controls (p = 0.003). For 1mmHg increase Uric Acid, 0.94 mmHg in pulmonary artery pressure level will increase. There was no significant difference between patients with PH and patients without PH according to age, gender, BMI, MAP, GFR, EF, RV size & function, LV diastolic dysfunction, SMRV, and TAPSE. Conclusion: Control of high Uric Acid levels and the treatment of risk factors of PH for prevention PH seems reasonable.